Do mental wellbeing and emotional eating influence BMI similarly or differently? Evidence from a sample of Peruvian adolescents - Cuyan-Zumaeta, Keisler; Javier-Aliaga, David; Rodríguez-Vásquez, Mery; Saintila, Jacksaint (Frontiers in Public Health, 2025)
BackgroundThe literature highlights that both mental wellbeing and emotional eating are closely related to BMI, but little is known about how these variables interact similarly or differently. Therefore, the aim of this study was to determine the predictive role of mental wellbeing and emotional eating on body mass index (BMI) in Peruvian adolescents.MethodsThis research used a non-experimental and predictive design. The sample consisted of 270 students aged 12–18 years from a public educational institution in the province of Tocache, Peru. The sample was selected through non-probability purposive sampling. The study employed the Mental Health Inventory (R-MHI-5), the Emotional Eating Scale (EES), and BMI was calculated using Quetelet’s formula.ResultsCorrelations revealed that mental wellbeing was negatively associated with BMI (r = −0.277, p < 0.001, 95% CI = [−0.384, −0.163]), whereas emotional eating was positively associated with BMI (r = 0.274, p < 0.001, 95% CI = [0.160, 0.381]). In the multiple regression analysis, Model 2 emerged as the most suitable (adjusted R2 = 0.112, F = 17.953, p < 0.001, BIC = 1,318), explaining 11.2% of the variance in BMI. Standardized coefficients indicated that mental wellbeing had a significant negative effect on BMI (β = −0.217, 95% CI = [−0.3353, −0.0997], p < 0.001), while emotional eating had a significant positive effect (β = 0.213, 95% CI = [0.0952, 0.3308], p < 0.001). Moreover, both coefficients showed similar magnitudes.ConclusionThe findings of this study confirm that mental wellbeing and emotional eating exert opposing yet similarly sized influences on BMI in Peruvian adolescents. These results underscore the importance of addressing both variables equitably in interventions aimed at improving adolescents’ nutritional status.